Original paperParaoxonase-1 activity and the levels of lipids and lipid peroxidation markers in arterial versus venous blood samples in coronary angiography patients - Göçmen, Ayșe Yeșim; Gűműșlű, Saadet; Gűnaydin, İlhan; Semiz, Ender (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
Introduction: The percutaneous catheterization of various arteries is used in visualization of coronary arteries. Aim: We aimed to determine whether arterial blood samples withdrawn from femoral arteries during standard Judkin’s technique in patients evaluated with coronary angiography can also be used to determine some biochemical parameters. Material and methods: In 50 controls (25 males and 25 females) and 73 coronary artery disease (CAD) patients (10 females and 63 males) paraoxonase-1 (PON1) activity, total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), very low-density lipoprotein cholesterol (VLDL-C), high-density lipoprotein cholesterol (HDL-C) and triglyceride (TG) levels were measured using colorimetric methods. Lipid peroxidation marker levels (conjugated dienes (CD) and thiobarbituric acid-reactive substances (TBARS)) were measured manually. Results: There was no difference in lipid and lipid peroxidation marker levels, PON1 activity and TC/HDL-C, LDL-C/HDL-C and PON1/HDL-C ratios between arterial and venous blood samples. LDL-C, CD and TBARS levels and TC/HDL-C and LDL-C/HDL-C ratios were significantly lower in both arterial and venous blood samples of controls compared with CAD patients. Paraoxonase-1 activity, HDL-C level and PON1/HDL-C ratio were higher in controls than CAD patients. On multiple logistic regression analysis, risk factors associated with CAD were found to be the levels of arterial CD, venous CD, arterial TBARS and arterial LDL-C/HDL-C ratios in CAD patients. Conclusions: Our study might indicate that arterial blood samples can also be used as well as venous samples to determine these parameters. On the other hand, elevated arterial lipid peroxides are associated with cardiovascular complications, presumably by decreasing PON1 activity.